ECC-Based Authenticated Key Agreement Protocol with Privacy Protection for VoIP Communications - Shaohui Zhu; Fan Yang; Liping Zhang; Shanyu Tang; Li, J. (2013 IEEE International Conference on Green Computing and Communications and IEEE Internet of Things and IEEE Cyber, Physical and Social Computing, 2013)
VoIP is a telephony application which transmits the compressed voice in packets over the Internet. The voice packets are subject to eavesdropping on the public network, since the Internet possesses the inherent security vulnerabilities. In order to protect users' privacy and voice packets confidentiality, an authentication module with encryption should be imposed during VoIP communications to ensure secure voice call. In this paper, we propose an authenticated key agreement protocol based on ECC. The proposed protocol negotiates the secret session key and then employs the well-known AES encryption algorithm to encrypt/decrypt the voice packets with the session key for privacy protection. We deploy the scheme on a SIP-based VoIP phone over the local network. The results from our experiments demonstrate that our proposed scheme not only provides secure VoIP call, but also preserves the quality of real-time voice, which is vital to VoIP applications.